PENGARUH CYBER SECURITY TERHADAP KESEHATAN MENTAL MAHASISWA PSIKOLOGI - Ardian Firdaus Saputra; Edy Soesanto, Muhammad Farid Alifianto, Difani Cahya Prastiwi (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The rapid development of Internet technology has led to the emergence of new crimes in this field, such as data manipulation, espionage, sabotage, provocation, money laundering, hacking, software theft or hardware theft and many other crimes. Even the level of internet crime (cybercrime) is not monitored by the government so it is difficult to control. The emergence of a number of cyber crime cases in Indonesia has become a threat to the stability of security and public order with a fairly high level of escalation. The aim of this research is to better understand technology so that it is not easily affected by cyber crime and that everyone's cyber security is better maintained. The method we used in preparing this research was literature study. The results of data information found from various journals show that cyber crime cases greatly affect the level of cyber security and mental health of each person.